PENGARUH LATIHAN MENEMBAK DARI KURSI TERHADAP HASIL TEMBAKAN FREE THROW - Iskurniawan, Moh Alief (Journal of Sport Coaching and Physical Education, 2016)
Techniques shot is an important technique, including shot free throw practice shooting free throw has been less noticed by the coach does not use training methods . Objective to know: 1) Knowing how much influence methods of practice shooting from a chair with a distance gradually and remain on the shot free throw on basketball players SMAN 1 Kendal, 2) Knowing how much influence the method of firing exercises permanent seat on basketball players SMAN 1 Kendal 2015. 3) Knowing the result of better training between the firing of the seat with a distance gradually and keep the results of free throws free throw on basketball players SMAN 1 Kendal.This research method using experiments with pattern MS (matched by subject). The study population as many as 14 players the son of SMAN 1 Kendal 2015.